The Effectiveness of Services to The Elderly in Public Health Center at Nakhon Sawan Municipality, Muang Nakhon Sawan District, Nakhon Sawan Province - Inthajit, Janjira; Sirichotiratana, Nithat; Prutipinyo, Chadsumon (Journal of The Royal Thai Army Nurses, 2021)
This study is a quantitative research to studying the efficiency of services for the elderly provided by public health centers in Nakhon Sawan Municipality, Muang Nakhon Sawan District, Nakhon Sawan. The subjects were 353 public health personnel or long-term public health care managers (CM), caregivers of dependent elders (CG) and village health volunteers (VHV). Data were collected using questionnaires and interview forms. Data were analyzed using statistics, mean, percentage, standard deviation and logistic regression analysis. According to the findings, the overall efficiency of the services for the elderly, provided by public health centers in Nakhon Sawan Municipality was high. Public health personnel or long-term public health care managers had a low mean score in training to review knowledge on healthcare for the elderly both physical and mental health ( = 2.20). Caregivers of dependent elders had a low mean score in nutrition appropriate for diseases ( = 2.50). village health volunteers had the lowest in taking the elderly who did not have caregivers, or relatives, to see a doctor ( = 3.25). According to logistic regression analysis, knowledge management had an effect on efficiency of services for the elderly increase by 1.151 times.